INCORPORAÇÃO DE POLIFENÓIS E ANTIOXIDANTES DE EXTRATOS DE ERVAMATE (Ilex paraguariensis) EM AMIDO DE CARÁ-MOELA (Dioscorea bulbifera Linn) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
Starch can be obtained most commonly from corn, wheat, rice and also tubers and roots. But other sources are being studied, such as starches extracted from the genus Dioscoreae spp., A species of this genus studied infrequently is the Dioscorea bulbifera Linn also known as gizzard. In this work the native starch of D. bulbifera Linn was obtained and modified with aqueous and hydroalcoholic extract in three different concentrations of yerba mate, Ilex paraguariensis, a plant rich in bioactive compounds responsible for its beneficial health properties. Using the techniques such as Differential Scanning Calorimetry (DSC), rheological analysis through the Viscoamilographic (RVA) analysis. Thermogravimetry coupled to the system Differential Scanning Calorimetry - Mass Spectrometry (TG-DSC-MS) and morphological ones such as Scanning Electron Microscopy (SEM), X-ray diffraction method (XRD) and Colorimetry, it was possible to verify the interaction of this starch of D. bulbifera Linn with the extracts obtained from the leaves of yerba mate. Initial gelatinization temperatures of the starches with 6% aqueous extract incorporation and with 6% hydroalcoholic extract were slightly higher in relation to the native starch when studied by DSC. Most of the samples presented values of Tp and Tc and gelatinization enthalpy near to the native one. In the RVA analysis it was observed that the peaks of viscosity were higher in modified starches with extract aqueous. The final viscosity and tendency to retrograde increased relative to the native. SEM images did not change, native starch staining had a greater tendency to white L * than those modified. The X-ray diffractograms showed starch type "C. In the TG-DSC-MS analysis the main events in the DSC were more intense in the treated samples, as well as the mass-load signals detected, measured by mass spectrometry, occurred with more intense events in the samples treated with hydroalcoholic extracts and in the m / z 58 was detected in all samples except native starch. Evidence that there was incorporation of the phenolic compounds with modification in the profile of the gases generated during the decomposition.
Keywords: análise térmica; compostos fenólicos; compostos biotivos; atividade antioxidante; espectrometria de massas; TG-DSC-MS; thermal analysis; phenolic compounds; bioactive compounds; antioxidant activity; mass spectrometry; TG-DSC-MS; CNPQ::CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS